Svet starih staršev - Mihalinec, Eva (Teorija in praksa, 2025)
Grandparents provide fundamental support for the nuclear family, adding substantially to its day-to-day functioning and intergenerational stability through their presence and assistance. The article presents the findings of qualitative analysis based on semi-structured, in-depth interviews with 25 grandparents, thus becoming the first study of grandparenting within the framework of social practices in the cultural context of Slovenia. The construction of the grandparent role as part of postmodern imperatives such as child-centeredness, active ageing, new fatherhood, and reflexive individualism is explored, while the shortcomings of relevant public policies are also highlighted. International research findings are corroborated by the findings, affirming that grandparents are not a homogeneous group and that grandparenting practices instead range from traditional to late-modern patterns.
Keywords: Družbena vloga; Družina; gender division of labour; intergenerational cooperation; late modernity; medgeneracijsko sodelovanje; modificirane družine; modified families; pozna modernost; spolna delitev dela; Stari starši